Characterization of Cubic AgSbS2 Nanostructured Flowers Synthesized by Microwave-Assisted Refluxing Method. (8th September 2013) - Tipcompor, Narongrit; Thongtem, Somchai; Thongtem, Titipun
Abstract : Cubic AgSbS2 nanostructured flowers of nanorods were successfully synthesized by microwave-assisted refluxing of AgNO3, Sb(CH3 COO)3, and L-cysteine (C3 H7 NO2 S) dissolved in ethylene glycol at the pH of 4, characterized by X-ray diffraction (XRD) and electron microscopy (EM). The 1.89 eV direct energy gap was determined by UV-visible absorption, including two 688 and 857 nm emission wavelengths by photoluminescence (PL) spectroscopy. A possible formation mechanism of AgSbS2 nanostructured flowers was also proposed according to the experimental results.